Risk Factor in Senile Xerosis - Mujahid, Sabila Izzatina Azmy (PROMOTOR, 2025)
Aging is a progressive process that affects the functionality and maximum capacity of all organs, including the skin. In the elderly population (age >65), skin aging leads to conditions like xerosis senilis, pruritus senilis, and senile comedones, which are commonly observed. Xerosis senilis, or dry skin, results from impaired skin barrier function, increased transepidermal water loss, reduced skin hydration, and decreased lipid components such as ceramides, cholesterol, and free fatty acids in the stratum corneum. These factors make the skin more susceptible to infections, ulcerations, and chronic wounds. This condition manifests as dry, fissured, and rough skin, particularly on the extremities, and can progress to inflammation or infections, impacting quality of life through discomfort, stress, and daily activity interference. Xerosis affects approximately 50% of the elderly, with global prevalence ranging from 29.5% to 85%, correlating with increased age. While the exact risk factors for xerosis senilis remain unclear, genetic, environmental, and comorbid conditions such as hypertension, renal impairment, and diabetes mellitus are implicated. This review examines these risk factors and their mechanisms in contributing to xerosis senilis in the elderly population.